The Contribution of the Regional Security Systems for the Regional Security in South East Europe - Пудин, Константин (Научни трудове, 2020)
The Southeast European region is a highly interesting subject of study in regard to the security. It has a lot of specifics, which are determined by its geographic characteristics, the historical development of the countries located in it and in its immediate proximity, their current socio-economic development, and above all their ethnic, religious and cultural background. The purpose of the report is to present the main regional security systems (RSS) and their contribution to the regional security.